(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Necrotizing fasciitis, a surgical emergency, is a life-threatening soft tissue infection characterized by widespread, rapidly developing necrosis of the subcutaneous tissue and fascia. AIM: The aim of this study was to validate laboratory risk indicator for necrotizing fasciitis (LRINEC) score as a tool for early diagnosis and prognosis of necrotizing fasciitis and for differentiating NF from other soft tissue infections.. OBJECTIVE: To validate the LRINEC scoring system for the early diagnosis and prognosis of necrotizing fasciitis, for differentiating it from other soft tissue infections, to predict the mortality and amputation rateand to evaluate the incidence of necrotizing fasciitis inpatients with different co-morbid conditions. METHODS: A single centre, prospective cohort study was conducted on 140 patients from Department of General Surgery, JSS Hospital, Mysurufrom December 2020 to August 2022.Patients diagnosed with a soft tissue infection were included in this study. Initial assessment and risk stratification according to LRNIEC scoring system was done which was followed by appropriate conservative or surgical management. RESULTS:From the study population of 140 patients, 82 cases were clinically diagnosed as necrotizing fasciitis, 32 cases as cellulitis and 26 cases as spreading cellulitis. The results showed that there is significant correlation between LRINEC scoring system and prognosis of NF. It is a useful tool in predicting mortality and amputation rates in NF. It also demonstrates that among the study population, 68.6% of the patients had one or more co-morbidities with the most common being Type 2 Diabetes Mellitus (44.2%). CONCLUSION: LRINEC scoring system is a useful adjunct in the early diagnosis and prognosis of necrotizing fasciitis.Early detection of NF facilitates timely intervention thereby improving prognosis.